A tecnologia assistiva no ensino de química para cegos : interfaces para construção das representações mentais - Nascimento, Tânia Silva (2020)
This thesis presents discussions centered on Chemistry Teaching, Visual Impairment and Assistive Technologies and its general goal was to analyze the use of polychromatic tactile adhesive in the learning process of organic functions by a visually impaired student. The constant search for materials and methodologies capable of reaching all students in an inclusive and satisfactory way in the learning process of chemistry has undoubtedly been the driving force for a better development of people with visual impairments in the classroom. It is a qualitative case study research based on Yin perspective (2001), and the participants were one student with visual impairment, three students with no visual impairment, one brailist and one amblyope. The stages of the investigation include the construction of Assistive Technology, instrumental validation and application of the material with students from a state-maintained public school. The data collection instrument consisted of transcribed recordings, questionnaires, interviews using a semi-structured questionnaire, photographs, school activities and notes. For content analysis we used Bardin (2016). As theoretical subsidies, the research was based on the following theoreticians: Guijarro (2005), Januzzi (2006), Mazzota (2005) who discuss inclusion from a historical and conceptual perspective; Schwahn (2015), Raposo and Mol (2010), Pires et al (2007) who study the teaching of chemistry and visual impairment; Pitano and Noal (2018) and Ormelezzi (2000) who explain about the construction of mental representations; Bresch (2017) who explains about Assistive Technologies. The results corroborate the need for more refined reflections with regard to the construction and use of teaching materials so that the functionality is not reduced to mere instrumentalism. The analysis of the data allowed us to verify that even if the capacity for abstraction in blind people is superior when compared to people with no visual impairment, they need specific stimuli and concrete experiences mediated by appropriate methods and materials. The polychromatic tactile adhesive elaborated and applied, proved to be an ally in teaching organic functions as well as in stimulating the blind student to elaborate the mental image.